GESTÃO DO CONHECIMENTO: UM ESTUDO DE CASO DAS PRÁTICAS DE COMPARTILHAMENTO DO CONHECIMENTO DESENVOLVIDAS EM UMA EMPRESA PÚBLICA PAULISTA - DANIEL, IVETE ROLIM (2017)
This research has as main objective and general objective to understand how the practices of sharing of the knowledge management are applied in a public company of São Paulo. As a specific objective, to verify, analyze and identify the main reasons why the public company CETESB - Companhia Ambiental do Estado de São Paulo adopts knowledge, as knowledge sharing practice and the factors that favor or hinder the adoption of these practices and initiatives. In order to achieve this, we sought to gain a better understanding of the phenomenon that represents a set of processes that govern the creation, storage, dissemination and use of knowledge to achieve organizational excellence, based on the study of its main characteristics, the best way of sharing Knowledge. The study was developed under a qualitative approach, aiming at analyzing the existing approaches and models, indicating to the citizen taxpayers and the executives of the public organizations a panorama on the theme that generates new possibilities in the selection of actions related to the subject knowledge. The organization chosen for this study has invested in the construction and transfer of knowledge and in several improvements in its educational actions, fulfilling and ensuring excellence in its performance, mainly by the implementation of its higher school, strengthening its objectives, dissemination of knowledge, continuous updating and Encouraging the capacity for innovation through the sharing of knowledge. The method used was the case study with interviews and documentary analysis, which analyzed the knowledge sharing practices adopted by the organization, signaling to managers of public organizations, relevant aspects in this implementation and that will generate new alternatives for this public, In the adoption of knowledge sharing practices.